MITRAL VALVULAR INTERSTITIAL CELL RESPONSES TO SUBSTRATE STIFFNESS DEPEND ON AGE AND ANATOMIC REGION - Stephens, Elizabeth H. (2010)
The material properties of heart valves depend on subject age, disease state, and the complex valvular microarchitecture. Furthermore, valvular interstitial cells (VICs) are mechanosensitive, and their synthesis of extracellular matrix not only determines the valve's material properties but also provides an adhesive substrate for VICs. However, the interrelationship between substrate stiffness and VIC phenotype and synthetic properties is poorly understood. Given that the local mechanical environment (substrate stiffness) surrounding VICs differs among different age groups and different anatomic regions of the valve, it was hypothesized that there may be an age and valve-region specific response of VICs to substrate stiffness. Therefore, 6-week, 6-month, and 6-year-old porcine VICs from the center of the mitral valve anterior leaflet (MVAC) and posterior leaflet (PML) were seeded onto poly(ethylene) glycol hydrogels of different stiffnesses and stained for markers of VIC activation (smooth muscle alpha-actin (SMaA)) and collagen synthesis (heat shock protein-47 (HSP47), prolyl 4-hydroxylase (P4H)). 6-week-old MVAC demonstrated decreased SMaA, P4H, and HSP47 on stiffer gels, while 6-week-old PML only demonstrated decreased HSP47. 6-month-old MVAC demonstrated no difference between substrates, while 6-month-old PML demonstrated decreased SMaA, P4H, and HSP47. 6-year-old MVAC demonstrated decreased P4H and HSP47, while 6-year-old PML demonstrated decreased P4H and increased HSP47. In conclusion, the age-specific and valve-region-specific responses of VICs to substrate stiffness link VIC phenotype to the leaflet regional matrix in which the VICs reside. These data provide further rationale for investigating the role of substrate stiffness in VIC remodeling within diseased and tissue engineered valves.